Letter from Max Bredig to Kasimir Fajans, September 17, 1937 - Bredig, Max Albert (1937)
Max Albert Bredig (1902-1977) informs Kasimir Fajans (1887-1975) that he received a visa for the United States and will travel to New York next week. He plans say travel to Karlsruhe, Germany to say farewell to his family.
Keywords: Bredig, Max Albert, 1902-1977; Fajans, Kasimir, 1887-1975; Emigration and immigration